THE APPLICATION OF MODERN INNOVATIVE MANAGEMENT TECHNOLOGY IN THE MANAGEMENT OF EDUCATIONAL INSTITUTIONS (ІННОВАЦІЙНІ ПРОЦЕСИ ОСВІТНЬОЇ СФЕРИ УКРАЇНИ ТА КРАЇН ЦЕНТРАЛЬНОЇ ЄВРОПИ: СТАН, ПРОБЛЕМИ І ПЕРСПЕКТИВИ, 2024)
.